The Revision Surgery of the Digestive Tract after Failed Prior Gastric Reconstruction - V. Ruchkin, Dmitry; A. Kozlov, Valentin; N. Yan, Maria; A. Nitkin, Alexey; I. Nazaryev, Pavel; A. Rymar, Oleg (International Journal of Psychosocial Rehabilitation, 2020)
Aim: to develop an integrated concept of physiological reconstruction of the gastrointestinal tract by preserving the duodenal passage after failed prior gastric reconstructive surgery.Materials and Methods: 52 patients who had undergone resection, drainage, and anti-reflux surgery had redo operations performed between 2011 and 2017 at the A.V. Vishnevsky National Research Scientific Surgical Center. The redo surgery included different types of reconstruction: the Billroth-I for 5 patients (9.6%), the Hofmeister-Finsterer for 1 patient (1.9%), and Roux-en-Y reconstruction for 4 patients (7.7%) who had previous radical resection of the gastric stump. The surgical procedure of interposition of graft was done in 40 cases (76.9%): by the pedicled jejunal flap for 30 patients (57.7%), by the transverse colon graft for 2 patients (3.8%), and by the left colon graft for 8 patients (15.4%) after esophagectomy. 1 patient (1.9%), who had had prior gastric bypass surgery, underwent the resection of the tumor that affected the gastric pouch and the thoracic esophagus; the bypassed stomach was used as a gastric conduit for esophageal replacement. It was impossible to technically perform the reconstructive procedure in 1 case (1.9%) due to the absence of the visceral organs after multivisceral resection for the local recurrence of gastric cancer.Results: Post-operative complications were developed in 5 patients (9.6%). The esophagojejunal anastomosis leakage was observed in 2 patients (3.8%), and the duodenojejunal anastomosis leakage in 1 patient (1.9%). The transplant thrombosis was diagnosed on POD 1 in 1 patient (1.9%) and led to the colon graft necrosis, which required emergency transplant removal. It was the postoperative mortality rate that connected with the progression of the multiple organ dysfunction failure. At the end of the study, there were 44 (86.2%) patients out of 51 under observation. Patient examination revealed good results in 26 patients (59.9%) and satisfactory results in 12 patients (27.4%). The result of the redo surgery was failure in 6 cases (13.7%).Conclusion: The assessment of the results demonstrated the relief of pathological syndromes developed after gastric surgery in the majority of patients, which indicated the feasibility of redo surgery by inclusion of the duodenal passage.